Armet, an aphid effector protein, induces pathogen resistance in plants by promoting the accumulation of salicylic acid. (14th January 2019) - Cui, Na; Lu, Hong; Wang, Tianzuo; Zhang, Wenhao; Kang, Le; Cui, Feng
Abstract : Effector proteins present in aphid saliva are thought to modulate aphid–plant interactions. Armet, an effector protein, is found in the phloem sap of pea-aphid-infested plants and is indispensable for the survival of aphids on plants. However, its function in plants has not been investigated. Here, we explored the functions of Armet after delivery into plants. Examination of the transcriptomes of Nicotiana benthamiana and Medicago truncatula following transgenic expression of Armet or infiltration of the protein showed that Armet activated pathways associated with plant–pathogen interactions, mitogen-activated protein kinase and salicylic acid (SA). Armet induced a fourfold increase in SA accumulation by regulating the expression of SAMT and SABP2, two genes associated with SA metabolism, in Armet-infiltrated tobacco. The increase in SA enhanced the plants' resistance to bacterial pathogen Pseudomonas syringae but had no detectable adverse effects on aphid survival or reproduction. Similar molecular responses and a chlorosis phenotype were induced in tobacco by Armet from two aphid species but not by locust Armet, suggesting that the effector function of Armet may be specific for aphids. The results suggest that Armet causes plants to make a pathogen-resistance decision and reflect a novel tripartite insect–plant–pathogen interaction. This article is part of the theme issue 'Biotic signalling sheds light on smart pest management'.